Robust Binding of Disulfide-Substituted Rhenium Bipyridyl Complexes for CO2 Reduction on Gold Electrodes - Cattaneo, Mauricio; Guo, Facheng; Kelly, H. Ray; Videla, Pablo E.; Kiefer, Laura; Gebre, Sara; Ge, Aimin; Liu, Qiliang; Wu, Shaoxiong; Lian, Tianquan; Batista, Víctor S. (Frontiers in Chemistry, 2020)
Heterogenization of homogenous catalysts on electrode surfaces provides a valuable approach for characterization of catalytic processes in operando conditions using surface selective spectroelectrochemistry methods. Ligand design plays a central role in the attachment mode and the resulting functionality of the heterogenized catalyst as determined by the orientation of the catalyst relative to the surface and the nature of specific interactions that modulate the redox properties under the heterogeneous electrode conditions. Here, we introduce new [Re(L)(CO)3Cl] catalysts for CO2 reduction with sulfur-based anchoring groups on a bipyridyl ligand, where L = 3,3´-disulfide-2,2´-bipyridine (SSbpy) and 3,3´-thio-2,2´-bipyridine (Sbpy). Spectroscopic and electrochemical analysis complemented by computational modeling at the density functional theory level identify the complex [Re(SSbpy)(CO)3Cl] as a multi-electron acceptor that combines the redox properties of both the rhenium tricarbonyl core and the disulfide functional group on the bipyridyl ligand. The first reduction at -0.85 V (vs SCE) involves a two-electron process that breaks the disulfide bond, activating it for surface attachment. The heterogenized complex exhibits robust anchoring on gold surfaces, as probed by vibrational sum-frequency generation (SFG) spectroscopy. The binding configuration is normal to the surface, exposing the active site to the CO2 substrate in solution. The attachment mode is thus particularly suitable for electrocatalytic CO2 reduction.